USM-RICD CONTRIBUTES 30 SPECIALLY-MODIFIED WHEELCHAIRS FOR PERSONS WITH DISABILITIES (OKU) - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
BANGI, 6 August 2015 Universiti Sains Malaysia (USM) continues to enhance the universitycommunity network by working together with the Rajanagarinda Institute of Child Development (RICD), Thailand to contribute 30 speciallymodified wheelchairs to a group of persons with disabilities (OKU).